Performance Study of the Mobile IPv6 Protocol and its Variations - Christos Bouras; Kostas Stamos; G Aristomenopoulos (6th International Symposium on Communication Systems, Networks and Digital Signal Processing – CSNDSP 2008, Graz, Austria, 2008)
In this paper, we use the OMNET++ simulator in order to evaluate the performance of the basic Mobile IPv6 protocol and some of its proposed variations. The most important metric we are interested in is the handover latency, which is measured for various combinations of the proposed Mobile IPv6 variations and then this metric is used, combined with factors such as the complexity of the implementation, in order to evaluate and identify the best possible configuration for the operation of the protocol.